Pengaruh Intellectual Capital, Kinerja Keuangan Dan Operating Capacity Terhadap Financial Distress Dengan Siklus Hidup Perusahaan Sebagai Variabel Moderasi : (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Desy Pri Cahaya Sibarani; Nera Marinda Machdar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
In the current economic development, every company must be able to compete fiercely and toughly in the business world. The tighter the competition faced, the greater the desire and motivation of each company to improve its company in achieving its respective targets and goals. This ongoing competition requires every company to be able to maintain its business excellence. The business excellence of a company can be seen from how a company has the values ​​of knowledge, expertise, innovation and other intellectual assets owned by individuals, companies or organizations. Another advantage that can be assessed is how the company can carry out its operations well, and the extent to which a company can produce or produce goods or services. Apart from that, we can also see how a company can manage its finances well in achieving an entity's financial goals.